2007
DOI: 10.1038/oby.2007.619
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Cardiac Autonomic Function With Metabolic Abnormalities in Childhood Obesity

Abstract: KAUFMAN, CHRISTOPHER L., DANIEL R. KAISER, JULIA STEINBERGER, AARON S. KELLY, AND DONALD R. DENGEL. Relationships of cardiac autonomic function with metabolic abnormalities in childhood obesity. Obesity. 2007;15:1164 -1171. Objective: The objective was to examine cardiovascular autonomic (cANS) function and its potential relationships with leptin resistance, insulin resistance, oxidative stress, and inflammation in a pediatric sample with varying levels of obesity. Research Methods and Procedures: Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
95
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 37 publications
16
95
2
9
Order By: Relevance
“…Sekine et al 18 , analyzing HRV indexes in the frequency domain, suggest that they have more sympathetic activity and less parasympathetic activity as compared with eutrophic children, while Nagai et al 19 and Nagai & Moritani 20 observed both sympathetic and parasympathetic activities decreased in obese children. Yakinci et al 21 , using autonomic function tests, observed normal sympathetic activity and parasympathetic underactivity, and more recently, Kaufman et al 16 observed increase in LF/HF ratio and decreased HF index. Pascoal et al 22 found higher cardiac tone in the standing position when compared obese children with eutrophic children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sekine et al 18 , analyzing HRV indexes in the frequency domain, suggest that they have more sympathetic activity and less parasympathetic activity as compared with eutrophic children, while Nagai et al 19 and Nagai & Moritani 20 observed both sympathetic and parasympathetic activities decreased in obese children. Yakinci et al 21 , using autonomic function tests, observed normal sympathetic activity and parasympathetic underactivity, and more recently, Kaufman et al 16 observed increase in LF/HF ratio and decreased HF index. Pascoal et al 22 found higher cardiac tone in the standing position when compared obese children with eutrophic children.…”
mentioning
confidence: 99%
“…Studies have shown that obesity causes changes in the function of the autonomic nervous system in children and adolescents 16,17 . Such a condition of imbalance may represent a major negative factor since the autonomic function controls some of the internal functions of the body and, accordingly, deserves attention.…”
mentioning
confidence: 99%
“…Studies have shown that obesity produces abnormalities of the autonomic nervous system in children and young adults 21,22 . Autonomic behavior is assessed through Heart Rate Variability (HRV) a simple, non-invasive tool for the detection and study of cardiac irregularities in many conditions.…”
mentioning
confidence: 99%
“…www.intechopen.com The metabolism of food produces a shift in sympathovagal balance toward greater sympathetic modulation, similar to that associated with postural changes (Piccirillo et al 1998;Paolisso et al 2000;Martini et al, 2001;Rabbia et al, 2003;Guizar et al, 2005;Kaufman et al, 2007a;Kaufman et al, 2007b;Nagai and Moritani, 2004). Higher body mass index is associated www.intechopen.com with greater sympathetic responsiveness to postural changes, higher plasma leptin levels (Paolisso et al, 2000) and greater lipolytic activity of adipocytes (Berlan et al, 2002;Tentolouris et al, 2008).…”
Section: Discussionmentioning
confidence: 99%